PERANCANGAN SISTEM INFORMASI PENGELOLAAN DANA BANTUAN SOSIAL PADA SEKRETARIAT KORPRI KABUPATEN INDRAGIRI HILIR - Khairul Amaliah (JURNAL PERANGKAT LUNAK, 2021)
This research is conducted in the secretariat of KORPRI management council – Indragiri Hilir regency. The Purpose of this research are to find out, to apply and to build the work system of planning information system of social grants in KORPRI Secretariat Indragiri Hilir regency, Which will give the accurate and efficient information. This research is using Qualitative Descriptive method which describes the research result and analysis in order to dermine the conclusion. In this research, the method used by researcher are through the observation, interview, and documentations to see the clear result and discussion.